Sustainable Agriculture Practices in Uzbekistan: Investigating the Adoption and Impact of Sustainable Agricultural Practice - Rakhmonov Bekzod Sharibjon ugli (European Science Publishing, 2023)
Uzbekistan stands at the threshold of a remarkable transformation towards a market-based economy, leveraging the achievements of initial reforms. As the country progresses on this path, there is a unique opportunity to further enhance the transition by adopting a green approach, thereby fostering a more sustainable and inclusive economy. Green policies not only promote efficient resource allocation but also contribute to the development of competitive enterprises and the equitable distribution of benefits. Recognizing the vital connection between economic growth and environmental sustainability, the Government of Uzbekistan has taken a proactive stance by introducing the 'Strategy for the Transition to a Green Economy.